1999
DOI: 10.1038/sj.bjc.6690319
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis and transcript expression of the MEN1 gene in sporadic pituitary tumours

Abstract: The majority of pituitary tumours are monoclonal in origin and arise sporadically or occasionally as part of multiple endocrine neoplasia type 1 (MEN1). Whilst a multi-step aetiology involving both oncogenes and tumour suppressor genes has been proposed for their development, the target(s) of these changes are less clearly defined. Both familial and sporadic pituitary tumours have been shown to harbour allelic deletion on 11q13, which is the location of the recently cloned MEN1 gene. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 34 publications
0
21
0
3
Order By: Relevance
“…Moreover, we have been able to compare the data obtained in MEN 1 patients with those from 110 non-MEN1 patients with pituitary adenomas, matched for age, year of diagnosis, and follow-up period. On the basis of several reports that have shown that MEN1 germline mutation testing was not useful in isolated sporadic pituitary adenomas (21)(22)(23), no control subject had MEN1 mutation testing. However, each control subject had no other endocrine lesion than the pituitary tumor at the time of diagnosis, as during the follow-up period, and no family history of multiple endocrine neoplasia, attesting that control subjects were non-MEN1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have been able to compare the data obtained in MEN 1 patients with those from 110 non-MEN1 patients with pituitary adenomas, matched for age, year of diagnosis, and follow-up period. On the basis of several reports that have shown that MEN1 germline mutation testing was not useful in isolated sporadic pituitary adenomas (21)(22)(23), no control subject had MEN1 mutation testing. However, each control subject had no other endocrine lesion than the pituitary tumor at the time of diagnosis, as during the follow-up period, and no family history of multiple endocrine neoplasia, attesting that control subjects were non-MEN1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A minority is part of an autosomaldominant syndrome, multiple endocrine neoplasia type 1 (MEN1), which is associated with mutations in the MEN1 tumor suppressor gene. Others are associated with loss of heterozygosity on the 11q13 chromosome (2,(8)(9)(10). A dominant mutation occurs in the Gas gene in f30% of somatotrophinomas, but this mutation is rare in other pituitary tumors (2,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The combined results of 5 published reports reveal that mutations in the coding region or exon-intron boundaries of MEN-1 were present in only 8% (2 of 25) of sporadic somatotropinomas with LOH at 11q13 (30 -34). In addition, RT-PCR of total mRNA from 10 of these 23 tumors with LOH, but no MEN-1 mutation, revealed that the MEN-1 transcript was detectable in all (31,34,35), supporting the view that mutations in noncoding regions of MEN-1 or epigenetic mechanisms are unlikely to be involved in the pathogenesis of most somatotropinomas.…”
Section: Discussionmentioning
confidence: 67%